Soy Infant and Extensively Hydrolyzed Formula as Therapeutic Formula for Cow’s Milk Protein Allergy - Aldo Reynaldo; Badriul Hegar (The Indonesian Society for Digestive Endoscopy, 2014)
Cow’s milk protein allergy (CMPA) is a food allergy mostly suffered by children aged 3 years that can be mediated by IgE or non-IgE or both. The prevalence of CMPA in children is heterogeneous between populations. Meta-analysis study showed that the prevalence was 2-3% in infants and 1% in children aged 6 years. Although the prevalence is quite small but proper management is very important because it affects the quality of life of children and to avoid the risk of anaphylactic reaction that threatens life. Therapy for CMPA is to avoid cow's milk protein and its derivatives; it is also recommended for breast-feeding mothers to do the same. Therapeutic milk formulas that can be given is extensively hydrolyzed formula (eHF) or soy infant formula (SIF). The selection of formula became adebate, especially about the safety, effectiveness and cost. Keywords: cow milk protein allergy, soy infant formula, extensively hydrolyzed formula